Community Connections: Managing an Employee Volunteer Program - Marilyn K. Lesmeister; Anne Romero (EDIS)
FCS9236, a 5-page fact sheet by Marilyn K. Lesmeister and Anne Romero, describes how to successfully develop and manage a program where employees perform work in the community with some form of support and/or encouragement from their employer. Includes references and a table matching employee motives with recruitment strategies. Published by the UF Department of Family Youth and Community Sciences, July 2006.